Substrate with hard anti-reflective coating

By using a multi -layer structure and a low refractive index layer of oxidatively in the anti -reflector coating, the existing coating's scratch resistance and abrasion resistance of existing coatings are solved. Tolerance and anti -reflection effect.

CN119372645APending Publication Date: 2025-01-28SCHOTT AG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411005504.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-26
Filing Date
2024-07-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing anti-reflective coatings are prone to scratches and other damage when facing high wear loads, resulting in reduced light scattering, turbidity and anti-reflective effects.

Method used

Adopt a multi -layer anti -reflector coating, through the design of the alternate layer, a layer with different refractive indexes, of which at least one low refractive index layer consists of a composition x containing silicon oxide and oxide. Between 10WT % to improve the scratch resistance and wear resistance of the coating.

Benefits of technology

It significantly improves the scratch resistance and abrasion resistance of anti -reflex coating, reduces the reflection of the base, maintains a low refractive index in the visible spectral range, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372645A_ABST
    Figure CN119372645A_ABST
Patent Text Reader

Abstract

The invention relates to a preferably transparent substrate coated with an anti-reflective coating, to a method for producing a coated substrate, and to the use thereof. In particular, the invention relates to coated substrates which are coated with an anti-reflective coating which has high scratch resistance and abrasion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preferably transparent substrate coated with an antireflection coating, a method for producing the coated substrate and the use thereof. The invention relates in particular to a coated substrate coated with an antireflection coating which has a high scratch and abrasion resistance. Background Art

[0002] Interference optical coatings are now often used as anti-specular reflection coatings, i.e. as anti-reflection or anti-reflection or AR coatings to improve the transmission of transparent substrates (e.g. viewing windows or filters) or, on the other hand, to reduce interfering reflections on the substrate. However, depending on the intended use of the substrate, anti-reflection coatings can be subject to high abrasion loads. However, scratches and other damages lead to turbidity by light scattering, which reduces the anti-reflection effect of the coating by changing its coating and thus defeats the purpose of the anti-reflection coating.

[0003] The topmost layer of the layer stack of the antireflection coating is formed by a low-refractive layer, usually a silicon oxide layer SiO2. The disadvantage here is that the low-refractive silicon oxide layer is very soft compared to the usual high-refractive index materials. Therefore, it is precisely the topmost layer that wears away quickly. If the topmost layer is eroded, the high-refractive layer forms the surface. This leads to a reversal of the anti-mirror effect, and the layer now acts more like a dielectric mirror.

[0004] Therefore, an antireflection coating with high scratch resistance and wear resistance is required. EP 2 492 251 B1 describes the manufacture of an antireflection layer system particularly for the watch industry. In addition to the antireflection effect, the hardness of the AR system is improved in that a hard material layer consisting of a mixture of Si3N4 and aluminum is introduced as a high-refractive-index layer. Since watches and especially so-called magnifying glasses for date display that are bonded to watch glasses are often subjected to mechanical loads due to scratches, it is meaningless to use common antireflection layer systems, because these layer systems can be completely removed due to mechanical loads and produce reflections of the substrate material. The hard AR system developed based on EP 2 492 251 B1 provides an antireflection system that is significantly more resistant mechanically than conventional optical tempering treatments.

[0005] DE 10 2016 125 689 A1 and DE 10 2014 104 798 A1 describe AR systems of varying composition having layers with a high refractive index, wherein the layers according to DE 10 2016 125 689 A1 are amorphous and the layers according to DE 10 2014 104 798 A1 contain nanocrystals.

[0006] The prior art describes a layer system consisting of a hard, high-refractive-index layer and a low-refractive-index SiO 2. Due to the antireflection system, the SiO 2 must in any case form the final layer, but SiO 2 is not a hard material layer and therefore the last layer always forms the weak point of the system relative to the grinding medium. Summary of the invention

[0007] The object of the present invention is therefore to further improve the abrasion resistance of anti-mirror reflection layers, in particular to provide anti-reflection coatings whose final layer has an increased scratch resistance compared to the final layers of SiO2 used hitherto and at the same time exhibits no or only a slight change in the refractive index in the visible spectral range. In addition, the object of the present invention is to provide a layer system which reduces the reflection of a substrate.

[0008] This object is achieved by the subject matter of the independent claims. Advantageous embodiments and developments of the invention are specified in the respective dependent claims.

[0009] The invention relates in particular to a coated substrate having a multilayer antireflection coating on at least one side, the multilayer antireflection coating consisting of layers with different refractive indices, wherein layers with a higher refractive index alternate with layers with a lower refractive index, and wherein at least one layer with a lower refractive index consists of a composition X comprising silicon oxide and zirconium oxide, wherein the zirconium content in the metal and semiconductor components of the composition X is 0.2 to 10% by weight, preferably 0.2 to 5% by weight, particularly preferably 0.5 to 3% by weight.

[0010] A layer having a lower refractive index consisting of a composition X comprising silicon oxide and zirconium oxide and in which the zirconium content in the metal and semiconductor components in the composition X is 0.2 to 10 wt %, preferably 0.2 to 5 wt %, particularly preferably 0.5 to 3 wt %, is also referred to below as Zr:SiO x layer.

[0011] It is known in principle that pure ZrO2 has good mechanical resistance. However, a disadvantage of using ZrO2 in coating solutions is that ZrO2 has a very high refractive index of >2.2 and therefore cannot be used as a low-refractive-index layer in AR coatings. Therefore, in the prior art, this material is used only as a high-refractive-index layer in optical layer systems.

[0012] Surprisingly, it has been found that by adding only very small amounts of zirconium during the production of a coating composed of SiO2, for example by co-sputtering of Si and Zr or by sputtering of a SiZr alloy target, the mechanical properties of the resulting coating vary greatly, while the optical properties of the coating remain virtually unchanged. Thus, by suitable selection of the zirconium content in the coating, the refractive index can be adjusted such that Zr:SiOx The layer may be applied in an AR system as a low refractive index layer and / or as a final layer.

[0013] The higher the selected zirconium content in the coating, the higher the Zr:SiO x However, surprisingly, it was found that the refractive index of the layer from zirconium in Zr:SiO x From a certain threshold value of the zirconium content in the layer, the mechanical resistance to scratches in the coating deteriorates again when the zirconium content in the coating increases further. Therefore, it is surprisingly possible to produce Zr:SiO with optimal mechanical resistance and at the same time a sufficiently low refractive index. x In addition, this also has a positive effect on the coating costs, since Zr is a relatively expensive material and high SiO x The sputtering rate of the layer is higher than that of the high-content ZrO x The sputtering rate of the layer.

[0014] In this case, the composition X of the layer with a lower refractive index may also contain other components in addition to zirconium oxide and silicon oxide. If, for example, only silicon and zirconium are contained in the composition of the layer as metal and semiconductor components, the above-mentioned zirconium content in the composition X is equivalent to the following requirement:

[0015] 0.2≤(Zr / (Zr+Si)*100≤10,

[0016] Preferably 0.2≤(Zr / (Zr+Si)*100≤5,

[0017] Particularly preferably, 0.5≤(Zr / (Zr+Si)*100≤3,

[0018] wherein Zr is the zirconium content in the layer in wt %, and Si is the silicon content in the layer in wt %. x In the case where the layer composition X contains other metal and semiconductor components, the denominator is supplemented accordingly according to the above relationship.

[0019] Here, in principle, in Zr:SiO x In addition to silicon oxide and zirconium oxide, other components may also be included in the layer, such as aluminum, boron, titanium, nickel, tin, gallium, yttrium, hafnium, chromium and carbon. These components can be used in particular in the production of Zr:SiO x The Zr:SiO layer is introduced into the Zr:SiO layer in a targeted manner by doping the target material or by impurities in the target material during sputtering. x However, it is preferably provided that Zr:SiO x The layer consists at least 80 wt %, in particular 90 wt %, or even 95 wt % or 99 wt % of silicon oxide and zirconium oxide.

[0020] Zr:SiO x The layer thickness of the layer can be in the range from 10 to 300 nm, preferably in the range from 10 to 200 nm, particularly preferably in the range from 50 to 150 nm.

[0021] Anti-reflective coating

[0022] AR coatings are designed as interference optical coatings with a plurality of dielectric layers. In the sense of the present invention, dielectric layers are understood in particular to be layers with a low or high refractive index or layers with a relatively low or high refractive index, which contribute to the anti-specular reflection effect of the AR coating. The layer system of the AR coating alternately has layers with a low and high refractive index.

[0023] In one embodiment, the low-refractive-index layer has a refractive index in the range of 1.3 to 1.6, in particular in the range of 1.45 to 1.5, at a wavelength of 550 nm. This makes it possible to achieve a high anti-mirror reflection effect.

[0024] In one embodiment, the high-refractive-index layer has a refractive index in the range of 1.8 to 2.3, preferably in the range of 1.95 to 2.1 at a wavelength of 550 nm.

[0025] In one embodiment, the high-refractive-index layer has a layer thickness of 100 to 500 nm, preferably 100 to 300 nm, particularly preferably 100 to 200 nm, and in one embodiment, the low-refractive-index layer has a layer thickness of 60 to 200 nm, preferably 60 to 100 nm.

[0026] The uppermost dielectric layer or final layer is the layer with a low refractive index. Here, the uppermost layer is understood to be the layer with the greatest distance from the substrate.

[0027] Accordingly, the first or lowermost layer of the AR coating is the layer closest to the substrate and in one embodiment is arranged directly on the substrate. The refractive index of the lowermost layer is related to the refractive index of the substrate. If the refractive index of the substrate is higher than the refractive index of the low refractive index layer of the AR coating, the low refractive index layer is advantageous as the first layer of the AR coating. If the substrate has a refractive index equal to or lower than the low refractive index layer of the AR coating, the higher refractive index layer is advantageous as the first layer of the AR coating.

[0028] In the case of substrates with a relatively low refractive index, the AR coating preferably comprises at least four layers, for example four or six layers, in order to achieve a good scratch protection effect on the one hand and a good anti-mirror reflection effect on the other hand. Figure 1b or Figure 1d). It is therefore advantageous if the antireflection coating has at least two layers with a higher refractive index and at least two layers with a lower refractive index, wherein the layer with the higher refractive index is used as the first layer and the layer with the lower refractive index is used as the final layer ( Figure 1b ).

[0029] For example, the individual layers can have the following layer thickness ranges: 5 to 40 nm for the bottommost or first layer, 10 to 40 nm for the next or second layer, 100 to 200 nm, preferably greater than 120 nm, for the next or third layer (which, according to this variant, forms the second highest layer of the layer stack and therefore the highest high-refractive-index layer of the layer stack), and 40 to 120 nm, preferably 60 to 100 nm, for the topmost fourth layer.

[0030] like Figure 1b As shown by way of example in , the above-described layer design is particularly suitable for glass and glass ceramic substrates.

[0031] In the case of a substrate with a higher refractive index, the AR coating is formed by at least two layers of low refractive index and at least one layer of high refractive index. In this embodiment, the layer of high refractive index is arranged between two layers of low refractive index. For better anti-mirror reflection effect, the AR coating on the substrate with a higher refractive index is preferably composed of at least five ( Figure 1a ), seven ( Figure 1c ) or nine layers. Other layers can also be added, however, the cost of the AR coating increases with the additional layers.

[0032] According to a development of the invention, the substrate can have a curved, in particular lenticular, surface which is coated with the AR coating.

[0033] Composition of the layer with the lower refractive index

[0034] The AR coating comprises at least two, but usually three or more layers of low refractive index or layers with a lower refractive index. If two or more layers with a lower refractive index are present, these layers may have the same composition or different compositions.

[0035] At least one layer having a lower refractive index is Zr:SiO x Layer, preferably Zr:SiO x layer is used at least as the topmost or final layer. However, Zr:SiO x The layer may also be used for one or more additional low refractive index layers, or for all low refractive index layers of the AR coating.

[0036] Except for at least one Zr:SiO xLayer, however, one or more low-refractive-index layers with different compositions may also be present. According to one embodiment, such a low-refractive-index layer consists of SiO2 or doped SiO2. Doped SiO2 is in particular SiO2 doped with one or more oxides, nitrides, carbides and / or carbonitrides, which are selected from the elements aluminum, boron, titanium, chromium or carbon. Alternatively or additionally, the low-refractive-index layer may contain nitrogen.

[0037] According to one embodiment, the doped SiO2 is aluminum-doped SiO2, ie SiAlO2 with a silicon content of 1 to 99 wt%, preferably 85 to 95 wt%. x .

[0038] The addition of aluminum or aluminum oxide also gives the soft silicon oxide layer a higher scratch resistance and wear resistance. The aluminum doping should preferably not exceed 20 mol percent of the silicon content. In other words, it is preferred that the material ratio of aluminum to silicon is at most 0.2. Accordingly, for the material amounts of silicon or aluminum n(Si) and n(Al):

[0039] n(Al) / (n(Si)+n(Al))=x, wherein x is in the range of 0.05 to 0.2.

[0040] If the aluminum content is too large, the anti-specular reflection effect is reduced due to the increase in the refractive index of the low-refractive-index layer.

[0041] Composition of the layer with the higher refractive index

[0042] The AR coating comprises at least one, but usually two or more, layers of high refractive index or layers with a higher refractive index. If two or more layers with a higher refractive index are present, these layers may have the same composition or different compositions.

[0043] The high refractive index layer may comprise oxides, silicides, carbides or nitrides or combinations thereof of one or more metal and semiconductor components, such as silicon, boron, zirconium, titanium, nickel, chromium, tin, hafnium, gallium and / or yttrium. Examples are Si3N4, SnO2, AlN, AlN:SiN, which may be doped with other metal and / or semiconductor components.

[0044] According to one embodiment, the high refractive index layer can be silicon nitride Si3N4. In addition to silicon nitride, the layer can have at least one other component, for example one or more other nitrides, carbides and / or carbonitrides. Nitrides, carbides or carbonitrides are preferably corresponding compounds of the elements silicon, boron, zirconium, titanium, nickel, chromium and / or carbon. The corresponding mixed layer is also called a doped Si3N4 layer. The compound contained in addition to Si3N4 is called a dopant, wherein the content of the dopant can be up to 50wt%. Here, in the sense of the present invention, a doped layer is also understood to be a layer containing up to 50wt% of dopant.

[0045] As a high-refractive-index layer, a hard material layer with a high refractive index can also be used, which can be a pure aluminum nitride layer. Alternatively, such a hard material layer can also contain other components in addition to aluminum nitride, such as one or more other nitrides, carbides and / or carbonitrides. Nitrides, carbides or carbonitrides are preferably corresponding compounds of the elements silicon, boron, zirconium, titanium, nickel, chromium and / or carbon. The corresponding mixed layer is also called a doped AlN layer. The compound contained in addition to AlN is called a dopant, wherein the content of the dopant can be as high as 50 wt%. Here, in the sense of the present invention, a doped layer is also understood to be a layer containing a maximum of 50 wt% of a dopant.

[0046] In one embodiment, this high-refractive-index layer contains boron nitride in addition to aluminum nitride, that is, the layer is doped with boron nitride. The contained boron nitride reduces the coefficient of friction of the layer, which leads in particular to a higher resistance of the layer to polishing processes. This is advantageous not only with regard to the resistance of the correspondingly coated substrate during use by the end user, but also with regard to possible method steps in the further processing of the coated substrate.

[0047] According to another embodiment, a silicon-doped aluminum nitride coating (AlN:SiN) can also be used as a high-refractive-index layer, wherein the AlN content is preferably 75 wt % and / or the SiN content is preferably 25 wt %. Various properties of the AR coating, such as adhesion, hardness, roughness, friction coefficient and / or heat resistance, can be influenced by this AlN:SiN material system.

[0048] According to another embodiment, the high refractive index layer contains crystalline aluminum nitride with a hexagonal crystal structure with a main (001) preferred direction. The proportion of AlN in the hard material layer is preferably greater than 50 wt %. If the AlN of the hard material layer is crystalline or at least substantially crystalline and has a hexagonal crystal structure, a particularly scratch-resistant and wear-resistant and polishing load AR coating can be obtained. In particular, the AlN layer has a crystallinity of at least 50%. In order to use a high refractive index layer with a low refractive index layer in an interference optical system, the crystalline high refractive index layer must also have sufficient transparency. The high transparency of the crystalline high refractive index layer can be obtained in particular by the individual small-sized crystals in the layer. Therefore, for example, scattering effects are avoided by the small size. In one embodiment, the average crystal size is at most 20 nm, preferably at most 15 nm, and particularly preferably 5 to 15 nm. Another advantage of the small crystal size is the higher mechanical resistance of the layer containing the crystal. Therefore, larger crystals usually have dislocations in their crystal structure, which has an adverse effect on mechanical resistance. The AlN crystals in the hard material layer have a hexagonal crystal structure with a main preferred direction in the (001) direction, i.e. parallel to the substrate surface. In a crystal structure with a preferred direction, one of the symmetry directions of the crystal structure is preferably occupied by the crystal. In the sense of the present invention, an AlN crystal structure with a preferred direction in the (001) direction is particularly understood as a crystal structure that shows a maximum reflection in the range between 34° and 37° in the corresponding XRD spectrum in an X-ray diffraction measurement (measured at grazing incidence: GIXRD). Here, the reflection in this range can be assigned to an AlN crystal structure with a (001) preferred direction.

[0049] Properties of the coated substrate according to the invention

[0050] The coated substrates according to the invention exhibit good antireflection effects and at the same time have high mechanical resistance and abrasion resistance.

[0051] The high mechanical resistance can be seen, for example, from the fact that the residual reflection at a wavelength of 750 nm after mechanical loading according to the so-called Bayer test changes by up to 35%, preferably by up to 25%, relative to the reflection of the uncoated substrate, or the residual reflection of the coated substrate at a wavelength of 750 nm after the Bayer test is less than 5%, preferably less than 3%, particularly preferably less than 2.5%. In contrast, the interference optical coatings known from the prior art show a change of about 50% relative to the uncoated substrate.

[0052] In the Bayer test, 90 g of sand are filled into a coated substrate having a diameter of 30 mm and shaken 13,500 times on the substrate over a period of approximately 1 hour.

[0053] Another measure of the high mechanical resistance of the substrates coated according to the invention is the haze of the AR coating after the Bayer test, determined according to ASTM D 1003, D 1044. Preferably, after the Bayer test, the coated substrate has a haze which is at most 5% higher or even only at most 3% higher than the haze of the coated substrate before the Bayer test.

[0054] The scratch resistance of an AR coating depends not only on the hardness but also on how well the individual layers or sublayers adhere to one another and how well the AR coating adheres to the substrate. Furthermore, if the individual layers of the AR coating and / or the substrate exhibit different coefficients of thermal expansion, this can lead to stress formation in the AR coating and to flaking of the AR coating.

[0055] Zr:SiO as the final layer x The wear resistance of the layer and thus of the coated substrate according to the invention also depends on the ratio of the hardness and the elastic modulus of the corresponding layer. It is therefore preferred that the ratio of the hardness to the elastic modulus of the high-refractive-index layer is at least 0.08, preferably 0.1, particularly preferably greater than 0.1. This can be achieved by the (001) preferred direction. Similar layers with different preferred directions in their composition show relatively small values ​​in the range of 0.06 to 0.08.

[0056] Furthermore, the AR coating according to the present invention has excellent chemical resistance.

[0057] In this case, the antireflection coating of the coated substrate can have a martensitic hardness of 3.5 GPa to 7 GPa. The martensitic hardness can be determined here, for example, using the martensitic hardness test method according to DIN EN ISO 14577.

[0058] In a further development of the invention, it is provided that Zr:SiO x The layer has an elastic modulus (E modulus for short) of less than 150 GPa, preferably less than 100 GPa. x The layer can therefore be deformed relatively well. x The scratch prevention of the Zr:SiO layer is not only based on the high hardness of the coating, but also on the prevention of particle penetration into the Zr:SiO layer in the event of inelastic deformation or local damage of the coating. x In contrast, the particles intrude into the Zr:SiO x This may be partially permissible in the layer, since the resulting deformation of the coating can be realized essentially elastically and is therefore reversible and does not lead to the formation of scratches.

[0059] The low friction coefficient of the coating is usually directly related to the roughness of the coating surface. Here, the small roughness of the surface is also conducive to avoiding scratches, because the surface only provides a small action area for the forces acting parallel to the surface of the coating.

[0060] According to a development of the invention, the surface of the antireflection coating or the uppermost layer of the antireflection coating therefore has an average roughness and a root mean square roughness of less than 1.5 nm, preferably less than 1 nm, based on an area of ​​one square micrometer.

[0061] Anti-specular reflection with a reduction in reflectivity of more than 3% can achieve a neutral color impression. The reflectivity is largely below 1% in the visible spectral range.

[0062] Base

[0063] Transparent inorganic materials such as glass, and transparent and opaque glass ceramics, sapphire glass, Ti-doped synthetic quartz glass (fused silica) or crystals such as calcium fluoride for optical materials can be used as substrate materials. In addition, optical glass and filter glass or plastics for optical purposes can also be used as substrates. Alternatively, the substrate can also consist of borosilicate glass, aluminosilicate glass, soda-lime glass or lithium aluminosilicate glass, wherein this can also be a chemically or thermally toughened substrate.

[0064] Composite materials, in particular composite materials with glass, which are used, for example, as window glass for vehicles, are also suitable. Here, the composite body can also be produced after applying the anti-reflection coating. In order to produce such a composite body, for example, two glass plates are connected to each other by a PVB film.

[0065] application

[0066] The layer system of the antireflection coating according to the invention is advantageous in all places where the antireflection layer system is subjected to mechanical loads. Possible applications are applications in vehicle windshields including aircraft, cooktops or similar household appliances made of glass or glass ceramics, applications in the field of consumer electronics, such as covers for electronic displays and touch screens, and applications in watch glasses, which can have a flat or slightly curved surface. A curved watch glass can also be understood as a lens bonded or processed, for example, to a date display on a watch glass, which has, for example, a diameter of 7 mm and an arrow height, that is, the height of the lens from an imaginary plane on the edge of the curved surface to the vertex of the curved surface is 0.4 mm. In the case of such a slightly curved watch glass, the antireflection coating according to the invention can also be coated with a long-life scratch-resistant protection.

[0067] Furthermore, AR coatings for oven viewing windows, operating panels, work panels, and protective panels for use in the automotive, consumer electronics, mobile phones, watches, and smart watches sectors are also conceivable.

[0068] Therefore, the present invention also relates to a component or optical component comprising a coated substrate, wherein the component is preferably selected from components for the aforementioned application fields and is further preferably selected from the group consisting of watch glasses, optical components, head-up displays, eyewear devices for augmented reality, cooktops, and displays for smart watches, tablet computers or mobile phones or touch screens for smart watches, tablet computers or mobile phones.

[0069] Manufacturing method

[0070] The invention also relates to a method for producing such a coated substrate.

[0071] - wherein a multilayer antireflection coating is applied on at least one side of the substrate,

[0072] - by successively depositing a coating consisting of a plurality of layers with different refractive indices, wherein layers with a higher refractive index alternate with layers with a lower refractive index,

[0073] wherein at least one layer with a lower refractive index is applied, said layer consisting of a composition X comprising silicon oxide and zirconium oxide, wherein the zirconium content in the metal and semiconductor components of the composition X is 0.2 to 10 wt %, preferably 0.2 to 5 wt %, particularly preferably 0.5 to 3 wt %.

[0074] One or more AR coatings can be formed by sputtering on the surface of the substrate. Usually, a target is provided for sputtering, which comprises at least one metallic or semiconducting component. In this case, only targets consisting of metallic or semiconductor components can be used, as well as composite targets or alloy targets. In addition, only a single target can be used in sputtering, or two or more targets can be used, a so-called co-sputtering process.

[0075] Zr:SiO x The layer can also be applied to the surface of the substrate 101, for example, by sputtering. In this case, for example, co-sputtering of silicon and zirconium can be used to produce Zr:SiO with the addition of oxygen as a reaction gas. x The Zr content in the layer can be adjusted by adjusting the sputtering power. The higher the sputtering power is selected, the greater the sputtered Zr content and thus the greater the Zr content in the sputtered layer. According to this embodiment, the sputtering power can be at least 0.2 kW or at least 0.5 kW and / or at most 2 kW or at most 1.5 kW.

[0076] Furthermore, it is also possible to produce such layers in a sputtering process using SiZr alloy targets or SiZr composite targets with the addition of oxygen as reactive gas, wherein the composition ratio of the sputtering target preferably corresponds to the proportions of zirconium and silicon in the composition of the layer to be produced.

[0077] Similarly, further layers with a lower refractive index or layers with a higher refractive index may also be applied.

[0078] Depending on the combination of layers to be produced, the target can contain one or more elements selected from the group consisting of aluminum, silicon, boron, zirconium, titanium, nickel, chromium, yttrium, hafnium or carbon.

[0079] In addition to the above-mentioned sputtering methods, other physical and chemical coating methods can also be used for coating, such as, for example, ion beam sputtering, vapor deposition or chemical vapor deposition (CVD).

[0080] If SiO2 is provided as the further layer with a lower refractive index and Si3N4 as the layer with a higher refractive index, reactive sputtering is advantageous, since in this case both the silicon oxide for the layer with a low refractive index and the silicon nitride for the layer with a high refractive index can be produced using the same target. The switch to different layer materials can be made simply by changing the process parameters, in particular the composition of the process gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] The preferred design of the present invention is described in detail below with the help of the accompanying drawings. The accompanying drawings show:

[0082] Figure 1a-1d A schematic cross-section of an embodiment of a substrate coated with an AR coating is shown.

[0083] Figure 2 The improvement of the mechanical properties of three coated substrates according to the invention (Examples 1, 2 and 3) relative to a SiO2 reference (Comparative Example 1) is shown.

[0084] Figure 3a-3c The SiO2 reference ( Figure 3a ), according to Example 3 ( Figure 3b ) of the coating according to the present invention and according to Comparative Example 2 ( Figure 3c ) after performing the above-mentioned scratch test.

[0085] Figure 4a-4b The SiO2 reference (Comparative Example 1, Figure 4b ) of the scratch test, according to Example 2 ( Figure 4a ) of Zr:SiO x coating.

[0086] Figure 5A curve of the refractive index of the AR coating from Example 2 is shown.

[0087] In the following, features that are similar or identical to each other will be denoted by the same reference numerals. DETAILED DESCRIPTION

[0088] Figure 1a-1d Schematic diagrams of cross-sectional views of exemplary coated articles 100 are shown, wherein the coated articles 100 have a substrate 101 and an AR coating 102, respectively. The AR coating 102 alternately includes low refractive index layers 103, 103', 103" and high refractive index layers 104, 104', 104". The final layer 105 is part of the AR coating and is also a layer with a lower refractive index. At least one of the layers 103, 103', 103", 105 with a lower refractive index is a low refractive index Zr:SiO x Preferably, at least the final layer 105 is a low-refractive Zr:SiO x layer.

[0089] exist Figures 1a to 1d Four different variations of coated articles 100 are shown in FIG.

[0090] exist Figure 1a and Figure 1c In a variant of the present invention, the substrate 101 has a higher refractive index than the layers 103, 103', 103", 105 of the AR coating 102 with a lower refractive index. Therefore, the lowermost layer closest to the substrate consists of the layer with the lower refractive index. Alternatingly, the lowermost layer 103 with a lower refractive index is followed by layers 104, 104', 104" with a higher refractive index and a layer 103' with a lower refractive index and, if necessary, a layer 103" with a lower refractive index, until a five-layer or seven-layer AR coating is formed, in which the final layer 105 with a lower refractive index forms the topmost layer.

[0091] exist Figure 1b and Figure 1d In a variant of the present invention, the refractive index of the substrate 101 is equal to or lower than the refractive index of the layers 103, 103', 103", 105 of the AR coating 102 with a lower refractive index. Therefore, the lowermost layer closest to the substrate is composed of the layer 104 with a high refractive index. Alternatingly, the lowermost layer 104 with a high refractive index is followed by layers 103, 103' with a lower refractive index and layers 104' with a higher refractive index and, if necessary, layers 104" with a higher refractive index, until a four-layer or six-layer AR coating is formed, in which the final layer 105 with a lower refractive index forms the topmost layer.

[0092] Preferably, at least the layer 105 and, if applicable, also the further layers 103, 103', 103" with a lower refractive index are low-refractive-index Zr:SiO x layers, i.e. they consist of a composition X, wherein the composition X contains silicon dioxide (SiO2) and zirconium dioxide (ZrO2), wherein the zirconium content in the metal and semiconductor components in the composition X is 0.2 to 10 wt%, preferably 0.2 to 5 wt%, particularly preferably 0.5 to 3 wt%.

[0093] This low refractive index Zr:SiO x The layer of and other layers of the AR coating can be applied to the surface of the substrate 101, for example, by sputtering. In this case, for example, co-sputtering of silicon and zirconium can be provided with the addition of oxygen as a reaction gas to produce a low-refractive-index Zr:SiO x Furthermore, such a layer can also be produced in a sputtering process by adding oxygen as a reactive gas using a SiZr alloy target, wherein the composition ratio of the sputtering target preferably corresponds to the composition of the layer to be produced.

[0094] As explained previously, the substrate 101 may in particular be optical glass, filter glass or sapphire or sapphire glass.

[0095] The structure is a low refractive index Zr:SiO x The final layer 105 of the layer of ZrO2 has very good mechanical properties in terms of avoiding scratches compared to the usual SiO2 final layer, which is caused by doping the layer consisting essentially of SiO2 with a defined proportion of ZrO2. Figure 2 The effect of doping with ZrO2 is explained.

[0096] Here, Figure 2 It is shown that in the Zr:SiO x Influence of the zirconium-silicon ratio on the refractive index n and the improvement in mechanical properties (in percentage) in an exemplary coated substrate with a layer of SiO2 as final layer. Here, the ratio of zirconium to silicon is plotted as wt% of the reference metal matrix on the horizontal axis, while the improvement in mechanical properties is plotted as percentage on the vertical axis on the left. Here, the individual measured values ​​of the improvement in mechanical properties are shown by a bar graph. Here, two bars represent the following measured values ​​for each measuring point, which are determined at different positions of the AR coating. In order to determine the improvement in mechanical properties, a test was selected in which sand was used as a grinding medium. The percentages given describe the reduction in the scratch area of ​​the coated substrate compared to a conventional final layer composed of SiO2 (SiO2 reference) when performing a scratch test.

[0097] like Figure 2As shown, all three examples according to the invention have improved scratch resistance compared to the SiO2 reference. However, the best effect of the improvement in scratch resistance is achieved at a content of about 3 wt%, while at lower contents, such as, for example, 2 wt%, or at higher contents, such as, for example, 4 wt%, the improvement in scratch resistance is less.

[0098] Figure 3a-3c The SiO2 reference ( Figure 3a ), according to Example 3 ( Figure 3b ) of the coating according to the present invention and according to Comparative Example 2 ( Figure 3c ) after performing the above-mentioned scratch test. Here, as a coating on the substrate, Figure 3b In the embodiment of the invention, a final coating based on SiO2 was used, which had a zirconium content of 3.0 wt. % and a silicon content of 97.0 wt. % and a layer thickness of 91 nm, which was applied to one side of the substrate by means of a sputtering process. Figure 3a )and Figure 3b ) can be clearly seen that, although the test conditions are the same, the coating has Figure 3a The SiO2 reference has a significantly lower number of scratches. In particular, scratches extending only over a short distance can be significantly reduced. The AR coating with a higher Zr content according to comparative example 2 ( Figure 3c ) has a better performance than Example 2 according to the present invention ( Figure 3b ) significantly higher number of scratches.

[0099] Figure 4a-4b The SiO2 reference (Comparative Example 1, Figure 4b ) of the scratch test, according to Example 2 ( Figure 4a ) of Zr:SiO x coating. It can be seen that in the SiO2 reference ( Figure 4b ) has lost most of its coating, while Figure 4a In the case of the coated substrates according to the invention, only slight damage occurs on the coated surface, which does not impair the antireflection effect of the AR coating.

[0100] Example

[0101] Table 1 shows the results of AR coatings according to the present invention and comparative examples, which are formed by co-sputtering a silicon target and a zirconium target at different cathode powers, wherein the sputtering power on the silicon target is kept constant, while the power of the Zr target is varied as shown in Table 1.

[0102] Table 1

[0103]

[0104] All examples according to the invention show significantly improved scratch resistance compared to the comparative examples.

[0105] Reference numerals list

[0106] 100 Coated substrate

[0107] 101 Base

[0108] 102 Anti-reflective coating (AR coating)

[0109] 103, 103', 103" low refractive index layer

[0110] 104, 104', 104" high refractive index layer

[0111] 105 Final Layer

Claims

1. A coated substrate (100) having a multilayer antireflection coating (102) on at least one side, the antireflection coating consisting of layers with different refractive indices, wherein: Layers (104) with a higher refractive index and layers (103) with a lower refractive index alternate, wherein at least one layer with a lower refractive index consists of a composition X comprising silicon oxide and zirconium oxide, wherein the zirconium content in the metal and semiconductor components of the composition X is 0.2 to 10 wt %, preferably 0.2 to 5 wt %, particularly preferably 0.5 to 3 wt %.

2. The coated substrate according to claim 1, wherein The layer with a lower refractive index consisting of the composition X comprising silicon dioxide and zirconium oxide is the topmost layer (105) of the multilayer antireflection coating; and / or wherein the anti-reflection coating (102) has at least two layers (104) with a higher refractive index and at least two layers (103) with a lower refractive index; and / or wherein the layer (103) with a lower refractive index has a refractive index in the range of 1.3 to 1.6, preferably 1.45 to 1.5 at a wavelength of 550 nm, and / or the layer (104) with a higher refractive index has a refractive index in the range of 1.8 to 2.3, preferably 1.95 to 2.1 at a wavelength of 550 nm; and / or wherein the other layer (103) having a lower refractive index comprises SiO2 or doped SiO2 or SiO2 doped with Al; and / or wherein the layer (104) having a higher refractive index comprises an oxide, silicide, carbide or nitride of one or more metals and semiconductor components selected from aluminum, silicon, boron, zirconium, titanium, nickel, tin, hafnium and chromium or a combination thereof, preferably Si3N4, AlN, AlN:SiN or doped variants thereof; and / or wherein at least one layer (104) having a higher refractive index is a transparent hard material layer comprising crystalline aluminum nitride having a hexagonal crystal structure with a main (001) preferred direction; and / or Therein, the antireflection coating (102) has a total layer thickness in the range of 200 to 400 nm.

3. The coated substrate according to claim 1, wherein The substrate (101) has a curved surface coated with an anti-reflection coating.

4. The coated substrate according to claim 1, wherein The substrate (101) has a lens-shaped surface, and the lens-shaped surface is coated with an anti-reflection coating.

5. The coated substrate of claim 1, wherein: The substrate (101) is transparent.

6. The coated substrate of claim 1, wherein The substrate (101) is glass, optical glass, crystal for optical purposes, plastic for optical purposes or glass ceramic.

7. The coated substrate of claim 1, wherein: The substrate (101) is a glass selected from the group consisting of sapphire glass, borosilicate glass, aluminosilicate glass, soda-lime glass, synthetic quartz glass or lithium aluminosilicate glass.

8. The coated substrate of claim 1, wherein The substrate (101) is chemically or thermally tempered glass.

9. A method for producing a coated substrate according to any one of claims 1 to 8, wherein: applying a multi-layer anti-reflective coating on at least one side of the substrate (101), - the multilayer antireflection coating consists of layers with different refractive indices by successive deposition, wherein layers with a higher refractive index alternate with layers with a lower refractive index, - wherein the layer with the lower refractive index consists of silicon oxide with an aluminum content, and wherein at least one layer with a lower refractive index is applied, said layer consisting of a composition X comprising silicon oxide and zirconium oxide, wherein the zirconium content in the metal and semiconductor components of the composition X is 0.2 to 10 wt %, preferably 0.2 to 5 wt %, particularly preferably 0.5 to 3 wt %.

10. A component comprising a coated substrate according to any one of claims 1 to 8, the component being selected from the group consisting of a watch glass, an optical component, a head-up display, an eyewear device for augmented reality, a cooktop, and a display for a smart watch, tablet or mobile phone or a touch screen for a smart watch, tablet or mobile phone.

Citation Information

Patent Citations

  • Hard anti-reflective coatings, their manufacture and use

    DE102014104798A1

  • substrate comprising anti-reflection coating system with hard coating and method for its production

    DE102016125689A1

  • Substrate with antireflective coating and method for producing same

    EP2492251B1